(untitled) (EAAE Annual Conference Proceedings, 2023)
The paper aims to explore the potentials of research by design in architecture and visual arts. The main objective of the paper is to analyse the different models and epistemological positions advanced in the academic milieus as far as the doctoral research by design is concerned, to explore the differences and similarities between the research by design in the field of architecture and in the field of visual arts.